The Role of Civilizational Jurisprudence in Enhancing Wasathiyyah Islam and Religious Moderation an Indonesia: A Critical-Transformative Perspective - Fauzi, Moh Nur (JURNAL AT-TURAS, 2025)
Civilizational Jurisprudence has emerged as a crucial topic of discussion in Indonesia in recent years. Rapid global transformations and national dynamics have driven PBNU to introduce this discourse. Key global and national concerns include prolonged armed conflicts, radicalism and terrorism, climate change, geopolitical shifts, economic disparity, counter-discourses against the Republic of Indonesia and Pancasila, equitable economic distribution, and the reinforcement of Indonesian cultural identity. Against this socio-global backdrop, this study aims to conceptualize a Critical-Transformative Civilizational Jurisprudence framework to strengthen Wasathiyyah Islam and religious moderation in Indonesia. This research employs a literature review method, utilizing the latest data from various media sources. The analysis is conducted through a descriptive-analytical approach with a discourse analysis technique (content analysis) to examine the emerging narratives and conceptual developments. The findings indicate that Civilizational Jurisprudence plays a significant role in reinforcing Wasathiyyah Islam and religious moderation in Indonesia through two primary channels: cultural and structural strategies